Spectrophotometric determination of leukocytes in blood - Kuzu-Karsilayan, H; Eryilmaz, E; Yillar, G; Deniz, G; Yanikkaya-Demirel, G (WILEY-LISS, 2002)
The determination of leukocyte concentration in human blood depending on the detection of oxidized o-dianisidine in acidic solution is studied. The oxidation of o-dianisidine was carried out by peroxidase enzymes found in leukocytes. The reaction was stopped by the addition of 4N H2SO4 to the solution, and a very stable, colored o-dianisidine derivative was obtained. The calibration graph was plotted with the recorded absorbance values at 400 nm assigned to the y-axis, and leukocyte counts in 1-mL blood samples to the x-axis. The equation of the calibration graph was y=0.0025x+0.0904, with a correlation coefficient of R=0.994. The coefficient of variation and P-value of the method were 4.00% and 0.05%, respectively. (C) 2002 Wiley-Liss, Inc.
Keywords: leukocyte; O-dianisidine; human blood; spectrophotometry; SINGLET OXYGEN PRODUCTION; HUMAN-NEUTROPHILS; 5-LIPOXYGENASE ACTIVITY; EOSINOPHIL PEROXIDASE; MYELOPEROXIDASE; INHIBITION; ELASTASE; CHLORINATION; OXIDATION; CHLORIDE; Medical Laboratory Technology